Beauty and Social Interest Matter: Effects of Male’s Facial Attractiveness, Vocal Attractiveness and Social Interest on Female’s Decisions in Three-Person Games - Junchen Shang; Yizhuo Zhang (Behavioral Sciences)
Facial attractiveness, vocal attractiveness, and social interest influence two-person decision making. However, it remains unclear how these three factors jointly influence three-person bargaining. We investigated the impact of facial attractiveness, vocal attractiveness, and social interest on fairness decisions in a three-person ultimatum game and a third-party punishment dictator game. The results of the ultimatum game showed that in the condition of positive social interest, the acceptance rate of unfair/fair offers was higher when third players had attractive faces or attractive voices. Attractive faces of third players also increased acceptance rates of unfair/unfair offers than unattractive faces when third players expressed negative social interest. In the third-party punishment game, participants rated unfair allocations from unattractive-voice proposers with attractive faces (compared to unattractive faces) and proposers who expressed negative social interest (compared to positive social interest) as more reasonable. Regarding the punishment intentions, among the three factors, both the effect of vocal attractiveness and social interest were modulated by the combinations of the other two factors, while the effect of facial attractiveness remains robust across all conditions. These findings suggest that fairness decisions in three-person bargaining games are affected by beauty premium and social interest, while these effects vary across different decision contexts.